An introduction to German pietism : Protestant renewal at the dawn of modern Europe - Shantz, Douglas H (Baltimore : Johns Hopkins University Press, 2013)
An Introduction to German Pietism provides a scholarly investigation of a movement that changed the history of Protestantism. The Pietists can be credited with inspiring both Evangelicalism and modern individualism. Taking into account new discoveries in the field, Douglas H. Shantz focuses on features of Pietism that made it religiously and culturally significant. He discusses the social and religious roots of Pietism in earlier German Radicalism and situates Pietist beginnings in three cities: Frankfurt, Leipzig, and Halle. Shantz also examines the cultural worlds of the Pietists, including Pietism and gender, Pietists as readers and translators of the Bible, and Pietists as missionaries to the far reaches of the world. He not only considers Pietism's role in shaping modern western religion and culture but also reflects on the relevance of the Pietist religious paradigm of today. The first survey of German Pietism in English in forty years, An Introduction to German Pietism provides a narrative interpretation of the movement as a whole. The book's accessible tone and concise portrayal of an extensive and complex subject as well as its accompanying appendices with translations of German primary sources and discussion questions make it ideal for courses on early modern Christianity and German history. Book jacket
Issues in defining and describing the Pietist movement -- German radicalism and Orthodox Lutheran reform -- The thirty years war, seventeenth-century Calvinism, and reformed Pietism -- Beginnings of Lutheran Pietism in Frankfurt, 1670 to 1684 -- Conventicles and conflicts in Leipzig and the second wave, 1684 to 1694 -- Halle Pietism and universal social reform, 1695-1727 -- Radical German Pietism in Europe and North America -- Pietism and gender -- Pietism and the Bible -- Pietism, world Christianity, and missions to South India and Labrador -- The contribution of German Pietism to the modern world -- Reflecting on the cultural and religious legacy of German Pietism
Includes bibliographical references (pages 453-475) and index
Keywords: Pietism -- Germany